Pengaruh program tanggung jawab sosial perusahaan terhadap citra PT. Unilever Indonesia: Survey pada mahasiswa STIE PBM Jakarta - Machmed Tun Ganyang (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This article aims to discover the role of the Unilever For Indonesia Corporate Social Responsibility (CSR) program (Unilever's hashtag for Indonesia) in assisting micro, small and medium enterprises in Indonesia to continue selling in healthy and safe conditions. The main objective of this program is to support the survival of MSMEs amid a pandemic that hit not only Indonesia but also on a global scale. This research approach is quantitative associative, which examines the relationship between two independent and dependent variables. The sample was 71 students of the College of Economics, Business Development and Management (STIE PBM) East Jakarta. The results of this study indicate that the CSR program carried out by PT. Unilever Indonesia, Tbk. have a positive and significant impact on the company's image.